2005
DOI: 10.3402/ijch.v64i3.17987
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization, migration and alcohol use in a population of Greenland Inuit

Abstract: Our findings suggest that the alcohol intake among Inuit, living in Denmark and in Greenland respectively, differs in relation to total intake, drinking patterns and a measure of alcohol dependence. Whether this may be attributed to urbanization, or to migration, is not clear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…Previous studies have largely found that migrants face significant psychological and social stress due to unstable living conditions, changes in lifestyle, social alienation, insecure employment, poor working conditions, long working hours, and adapting to a new environment; Both population and laboratory based studies confirm that these social stresses are linked to health risk behaviors, particularly an increased urge to smoke and drink [2, 3, 46]. As a result, it was found that migrants engage in higher levels of risky behaviors, including alcohol use [712] and smoking [2, 13], when compared to rural inhabitants or the urban born population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have largely found that migrants face significant psychological and social stress due to unstable living conditions, changes in lifestyle, social alienation, insecure employment, poor working conditions, long working hours, and adapting to a new environment; Both population and laboratory based studies confirm that these social stresses are linked to health risk behaviors, particularly an increased urge to smoke and drink [2, 3, 46]. As a result, it was found that migrants engage in higher levels of risky behaviors, including alcohol use [712] and smoking [2, 13], when compared to rural inhabitants or the urban born population.…”
Section: Introductionmentioning
confidence: 99%
“…Higher levels of smoking and drinking are also associated with higher levels of personal disposable income - especially among adolescents [2, 2326], social isolation or a lack of support from families and friends [2, 10], and marriage or living arrangement [11, 27, 28]. Studies from a range of countries have consistently found males to be more likely to drink and to have a higher risk of becoming alcoholic than females [12, 19, 2830]. Previous studies have also revealed a strong influence of peer behavior on the smoking and drinking behavior of young people [31–33].…”
Section: Introductionmentioning
confidence: 99%
“…Studies from Greenland have shown associations between alcohol drinking patterns and social position (Jeppesen and Larsen, 2008), migration and urbanization (Madsen et al, 2005), and Sense of Coherence (Rossau and Svendsen, 2008). The present study shows that genetics must be added to the complicated list of causes of alcohol drinking patterns.…”
Section: Discussionmentioning
confidence: 96%
“…The data are subject to a number of limitations:

First of all, the number of alcohol-related deaths from natural causes in absolute terms is small and volatile.

Furthermore, total consumption of pure alcohol ignores differences and changes in consumption patterns. Alcohol intake is more concentrated in Greenland than in Denmark (2), but consumption has become more evenly distributed over time and across groups of the population, social and geographical. Thus, gender differences are diminishing in Denmark; there are no data for alcohol consumption of women and men separately in Greenland (23), but consumption for women and men is converging towards a common pattern (1).

…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol habits in Greenland differ from those in Scandinavian and European countries (2, 3), and the pattern of alcohol-related causes of death also differs. Cirrhosis of the liver is less prevalent whilst alcohol psychosis, alcoholism and alcohol poisoning are more prevalent than in Denmark (4).…”
mentioning
confidence: 97%